Uso de las TICS y su incidencia en la gestión administrativa de la Unidad Educativa Nicolás Infante Díaz del cantón Quevedo año 2017 - Villavicencio Veliz, Vilma Germania (2018)
The investigation showed that the lack of technological tools is one of the main axes of poor performance in Administrative Management in the Nicolás Infante Díaz. Educational Unit, which through surveys and interviews confirmed that the problem is due to a deficit of the ICTs. This situation affects the activities developed in the educational institution as a result of the lack of technology mastery, so due to this need, the design of a training workshop on the use of ICTs in Administrative Management is proposed. In order to improve user service in general. The TICS can become one of the pillars and the foundations of the current administrative management, it is necessary to offer the administrative personnel the knowledge that they must take into account in this reality. ICTs must be considered in two aspects: its knowledge and use. It is necessary to understand how it is generated, how it is stored, how it is transformed, how it is transmitted and how information is available in many manifestations (texts, images, sounds) according to the flow of users. ICTs should be used to facilitate administrative management, particularly through the Internet, using appropriate techniques. This requires a great effort of each personnel involved and an important work related to the planning and coordination of the administrative area team of the educational institution. Although it is a very motivating job, there are tasks everywhere, such as the preparation of the correct materials for the determined management, because generally there are no texts or educational products suitable for this type of teaching. Currently, it is considered that administrative management before the introduction of information technology in the Nicolás Infante Díaz. Educational Unit is of fundamental importance, especially when it is intended to be introduced in areas that involve the entire internal and external community of the same